Geese and grazing lawns: responses of the grass Festuca rubra to defoliation in a subarctic coastal marsh - O, Pamela C.; Kotanen, Peter M.; Abraham, Kenneth F. (Canadian Journal of Botany, 2007)
This is the accepted manuscript of an article published by the NRC Research Press. coastal marshes on James Bay and southern Hudson Bay, Canada, the grass Festuca rubra is heavily used for forage by Snow (Chen caerulescens caerulescens) and Canada Geese (Branta canadensis). On Akimiski Island, James Bay, this grass occurs in a mosaic of short, heavily-grazed patches and tall, lightly-grazed patches. We investigated whether short plants primarily are a plastic morphological response to grazing by geese. Over two growing seasons, we measured growth of short patches protected from grazing, and of tall patches subjected to mowing treatments, with unmanipulated short and tall controls. Protection resulted in rapid conversion from a short growth form to a tall form, similar in height and biomass to plants in tall control plots. Mowed tall plants also rapidly recovered to near tall control values for height and biomass. A single 3-week treatment episode often permitted nearly full recovery to tall form. In some cases, more sustained protection was required, but repeated mowing ultimately may have reduced growth rates. These results indicate that the morphology of individual plants of Festuca rubra plastically recovers from changes in defoliation pressure. Consequently, short patches likely represent grazing lawns maintained by intensive foraging by geese. This research was supported by the Ontario Ministry of Natural Resources (KFA) and is a contribution of the Wildlife Research and Development Section, an NSERC PGS-A and Northern Research Supplement (PCO), a Richard H.G. Bonnycastle Graduate Fellowship from the Institute for Wetlands and Waterfowl Research (PCO), the Northern Scientific Training Program of the Department of Indian Affairs and Northern Development (PCO), and an NSERC Discovery Grant (PMK).